Effect of Aloe binder on green properties of dry pressed copper compact: a comparative study - kumari J.; Mohanta K.; Singh V.K. (My University, 2025)
The present study used Aloe (0–4 wt%) as a binder for dry compaction of copper metal powder. The properties of copper compacts were investigated as a function of compaction pressure (130 MPa, 140 MPa, 150 MPa) and moisture content. The maximum compact density of samples was achieved using 3.5 wt% of Aloe binder at 150 MPa compaction pressure. The maximum achievable green and sintered density of the copper samples was 68.04% and 88.25%, respectively. The corresponding samples exhibited a 4.5-fold and 2.1-fold increase in their green and sintered flexural strength. Copper compacts with the optimal amount of Aloe binder were sufficient for green machining. The density and strength of green compacts were affected by plasticising effect of binder due to functional groups such as hydroxyl (−OH), carbonyl (C=O), and ester groups present in Aloe gel. Samples with the optimal amount of Aloe binder show minimum porosity with negligible residue, as validated by the SEM and thermal analysis. The examined results were compared with the green properties of dry-pressed copper compacts using 0–4 w % polyvinyl acetate binder. Copper has been selected due to its excellent electrical and thermal conductivity and corrosion resistance, making it valuable for electronics, heat exchangers, manufacturing components, etc. © 2025 Informa UK Limited, trading as Taylor & Francis Group.